THERMAL SPRAY POWDER FOR SLIDING SYSTEMS WHICH ARE SUBJECT TO HEAVY LOADS - GRIES, BENNO; BRUENING, BERNHARD (2014)
Die vorliegende Erfindung umfasst ein Verfahren zur Herstellung Chromnitridhaltiger Spritzpulver umfassend die folgenden Schritte: a) Herstellen oder Bereitstellen eines Legierungspulvers umfassend i) mindestens 10 Gew.-% Chrom und ii) mindestens 10 Gew.-% eines oder mehrerer weiterer Elemente(s) (A), ausgewählt aus den Nebengruppen IIIA bis IIB des Periodensystems sowie B, Al, Ti, Si, Ti, Ga, C, Ge, P und S, b) Nitridieren des Pulvers in Gegenwart von Stickstoff unter Ausbildung von CrN und/oder Cr2N. The present invention comprises a process for producing spray powders containing chromium nitride, comprising the following steps: a) preparing or providing an alloy powder comprising i) at least 10% by weight of chromium, and ii) at least 10% by weight of one or more additional elements (A) selected from the sub-groups IIIA to IIB of the periodic table as well as B, AL, Ti, Si, Ti, Ga, C, Ge, P and S, b) nitriding the powder in the presence of nitrogen under formation of CrN and/or Cr2N. La présente invention concerne un procédé de fabrication d'une poudre de projection contenant du nitrure de chrome, comprenant les étapes suivantes : fabrication ou fourniture d'une poudre d'alliage contenant i) au moins10 % en poids de chrome, et ii) au moins 10 % en poids d'un ou de plusieurs éléments additionnels (A) choisis parmi les groupes secondaires IIIA à IIB de la table périodique, ainsi que B, Al, Ti, Si, Ti, Ga, C, Ge, P et S, b) nitruration de la poudre en présence d'azote, dans des conditions entraînant la génération de CrN et/ou de Cr2N.